Adolescent gang involvement: The role of individual, family, peer, and school factors in a multilevel perspective. Issue 4 (6th October 2014) - Lenzi, Michela; Sharkey, Jill; Vieno, Alessio; Mayworm, Ashley; Dougherty, Danielle; Nylund‐Gibson, Karen
<x xml:space="preserve">Abstract</x> Youth gang involvement is a serious public health challenge as adolescents involved in gangs are more likely than others to engage in violence and aggression. To better understand gang involvement, we examined the role of protective (empathy and parental support) and risk (peer deviance and lack of safety at school) factors, as well as their interactions, in predicting adolescent gang affiliation. The study involved a sample of 26, 232 students (53.4% females; mean age = 14.62, SD = 1.69) participating in the California Healthy Kids Survey (CHKS), a survey investigating a wide range of youth health and risk behaviors administered in all California schools every 2 years. Using hierarchical linear modeling (HLM), findings indicated that high levels of empathy and parental support were associated with a lower likelihood of affiliating with a gang. Associating with deviant peers and perceiving the school as unsafe were positively correlated with gang membership. At the school level, lack of safety and type of school (special education, vocational, or alternative school vs. comprehensive schools) were associated with greater probability of gang membership. Empathy mitigated the association between deviant peers and gang membership. Aggr. Behav. 41:386–397, 2015. © 2014 Wiley Periodicals, Inc.